Corrosion behaviour of 316L stainless steel manufactured by selective laser melting. Issue 9 (26th March 2019) - Andreatta, Francesco; Lanzutti, Alex; Vaglio, Emanuele; Totis, Giovanni; Sortino, Marco; Fedrizzi, Lorenzo
Abstract: This work investigates the electrochemical behaviour of an AISI 316L stainless steel produced by selective laser melting (SLM) and compares its behaviour with that of wrought stainless steel with similar chemical composition. The SLM stainless steel specimens are tested in the as‐produced condition without stress relief or recrystallization heat treatments. The electrochemical tests are carried out in two electrolytes: 3.5 wt% NaCl solution with neutral pH and with pH of 1.8. At the macroscale, the microstructure of the SLM specimens is determined by the laser scanning pattern and displays an overlapping network of melt pools. At the microscale, the SLM specimens exhibit a cellular/columnar dendritic structure with submicrometric cell size. Electrochemical measurements highlight a more extended passive range for SLM stainless steel in both neutral and acid electrolytes indicating higher protective properties of the oxide film on SLM specimens. In contrast to the wrought material, the refined microstructure of the SLM specimens promotes a very shallow morphology of attack without deep penetration in the bulk. Abstract : The electrochemical behaviour of 316L stainless steel produced by selective laser melting (SLM) with optimized parameters is investigated in neutral and acid solutions. SLM specimens exhibit higher corrosion resistance than wrought 316L stainless steel with comparable chemical composition. The oxide film is more protective for SLM specimens in neutral and acid solutions.